Ameliorative effects of Ficus and Harrisonia diets on Small East African goat meat yield - Kalule Nampanzira, Dorothy; Kabasa, John David; Bakyusa Katongole, Constantine; Okello, Sam; Tabuti, John Robert Stephen (Small Ruminant Research, 2017)
The effect of supplements based on Ficus natalensis and Harrisonia abyssinica foliages on intake, growth and carcass yield of tethered goats was assessed on-farm using fourty growing intact male indigenous goats. Five diets were tested, which included the control (tethering on natural pastures), tethering supplemented with molasses (CM) and the three diets whereby tethering was supplemented with molasses as well as F. natalensis and H. abyssinica as follows: Harrisonia⁄ molasses (HM), Ficus⁄molasses (FM) and Ficus⁄Harrisonia⁄molasses (FHM). The supplements were formulated to supply crude protein (CP) and energy levels required for an average daily gain of about 50 g/day. Four farms in the same geographical location were used. Each farm had all the five diets with two goats per diet. The goats were tethered during the day (10:00–18:00 h) and the supplements offered overnight (after tethering). The dry matter (DM) intake from tethering ranged between 124 and 162 g/day, and was not affected (P > 0.05) the basal DM intake. However, the total DM and CP intakes were increased (P < 0.05) by supplementation with the browse foliages. The total DM and CP intakes were highest (P < 0.05) for FM (572 and 91 g/day, respectively) and FHM (638 and 102 g/day, respectively). Compared with the control, supplementation with browse foliages increased (P < 0.05) the average daily gain, hot carcass weight and dressing percentage by up to 37.2, 2.3 and 6%, respectively. Average daily gain was 17, 34, 45, 52 and 54 g/ day for control, CM, FM, HM and FHM, respectively. The hot carcass weight was 6.9, 8.2, 8.8, 9.1 and 9.2 kg for control, CM, FM, HM and FHM, respectively. In conclusion, Ficus natalensis and Harrisonia abyssinica foliages have the potential to be used as low cost protein supplements in low-input goat feeding systems. However, there is need to establish best presentation methods of the browse foliages to the goats.
Keywords: Carcass yield; Growth rate; Indigenous goats; Tethering; Ficus natalensis; Harrisonia abyssinica